Heavy metal detection in water using MXene and its composites: A review - Mohanadas, Dharshini; Rohani, Rosiah; Sulaiman, Yusran; Abu Bakar, Suriani; Mahmoudi, Ebrahim; Zhang, Lai-Chang (Elsevier, 2023)
Heavy metals, i.e., copper (Cu), lead (Pb), cadmium (Cd), chromium (Cr), mercury (Hg), zinc (Zn), and nickel (Ni), are the most common water pollutants that can cause severe impacts on human health, aquatic life, and ecosystems. Numerous efforts, including spectroscopic, electrochemical, and optical techniques, have been executed to identify and monitor the level of pollutants in water sources. The properties, role, as well as the electrochemical performance of the graphene and its derivatives, have been clearly elucidated for heavy metal detection, as presented in this review. MXene is a 2D hydrophilic material with abundant surface functional groups, narrow interlayer spacing, and great mechanical and thermal properties. MXene implies great catalytic activities towards various water pollutants due to the presence of different functional groups (-O and –OH) and a high surface area that offers abundant active sites for a direct ion-exchange process. The advanced development of MXene and MXene-based composites are highlighted in this review, specifically for heavy metal detection, mentioning the properties, synergistic effect, and detection performance. The challenges and future outlook of MXene in the field of sensor applications have been emphasized. This review presented an insight into possible features of MXene and its composites for heavy metal detection in water.